2021
DOI: 10.3390/polym13162789
|View full text |Cite
|
Sign up to set email alerts
|

Ethylic Esters as Green Solvents for the Extraction of Intracellular Polyhydroxyalkanoates Produced by Mixed Microbial Culture

Abstract: Volatile fatty acids obtained from the fermentation of the organic fraction of municipal solid waste can be used as raw materials for non-toxic ethyl ester (EE) synthesis as well as feedstock for the production of polyhydroxyalkanoates (PHAs). Taking advantage of the concept of an integrated process of a bio-refinery, in the present paper, a systematic investigation on the extraction of intracellular poly(3-hydroxybutyrate-co-3-hydroxyvalerate), produced by mixed microbial culture by using EEs was reported. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…As expected from the recovery data (see Figure 3 ), the lowest A PHA values were computed from the DRIFT spectra of samples A and B. Thus, digestion with NaOH produced PHA with significant amounts of residues, which was expected because similar trends were noted for wet biomasses [ 35 ] or other biomasses with similar PHA content [ 26 ]. The FTIR analysis shows that mastication was effective in reducing the amount of non-PHA residues in the extracted films.…”
Section: Resultssupporting
confidence: 67%
“…As expected from the recovery data (see Figure 3 ), the lowest A PHA values were computed from the DRIFT spectra of samples A and B. Thus, digestion with NaOH produced PHA with significant amounts of residues, which was expected because similar trends were noted for wet biomasses [ 35 ] or other biomasses with similar PHA content [ 26 ]. The FTIR analysis shows that mastication was effective in reducing the amount of non-PHA residues in the extracted films.…”
Section: Resultssupporting
confidence: 67%
“…Comparable studies have reported that ethyl acetate has been successfully used as a solvent for the extraction of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (P3HB-co-3HHx) containing >15 mol% of HHx, resulting in a recovery yield of 99 wt% at 100°C ( Riedel et al, 2013 ). Additionally, this study indicated the necessity to perform the extraction on dried cells since the presence of water had a double effect on ester hydrolysis and the reduction of the solvating power ( Alfano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, very high temperatures could have a negative impact on the yield. At very high temperatures, the produced PHB could be further decomposed into smaller molecules or organic acids that consequently decrease the extraction yield ( Aramvash et al, 2018 ; Alfano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In turn, the wide range of substrates suitable for MMC-PHA production manifests in the wide range of thermoplastic and elastomeric properties of the synthetized PHA, including poly(3-hydroxybutyrate) (P(3HB)), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (P(3HB-co-3HV)), copolymers with variable 3-hydroxyvalerate (3HV) content, poly(4-hydroxybutyrate) (P(4HB)) and related copolymers, and poly(3-hydroxyhexanoate) (P(3HH)) and related copolymers [40][41][42]. PHA's properties mainly depend on the length and composition of the side chains-the literature states that the addition of monomers such as 3HV, and less frequently 3HH, to a P(3HB) backbone causes a reduction in the crystallinity and the melting temperature, as well as increasing the flexibility [43]. Indeed, P(3HB) is a very highly crystalline and stiff material, but at the same time, it is also brittle; its melting temperature is generally higher than those of copolymers (around 170-180 • C) and close to the degradation temperature (165-170 • C) [44].…”
Section: Bioprocess For Pha Production From Terrestrial Bacterial Str...mentioning
confidence: 99%